Noble Gas Reactivity in Planetary Interiors - Sanloup, Chrystele (Frontiers in Physics, 2020)
While the field of noble gas reactivity essentially belongs to chemistry, Earth and planetary sciences have brought a different perspective to the field. Indeed, planetary interiors are natural high pressure (P) and high temperature (T) laboratories, where conditions exist where bonding of the heaviest noble gases may be induced thermodynamically through volume reduction (Le Châtelier's principle). Earth and planetary sciences besides generate numerous and precise observations such as the depletion of the terrestrial and martian atmospheres in xenon, pointing to the potential for Xe to be sequestered at depth, potentially induced by its reactivity. More generally, this paper will review the advances on noble gas reactivity at the extreme P-T conditions found within planetary interiors from experiments and theoretical investigations. This review will cover the synthesis of cage compounds, stoichiometric oxides and metals, and non-stoichiometric compounds where noble gases are only minor or trace elements but could be essential in solving some Earth and planetary puzzles. An apparent trend in noble gas reactivity with P emerges. In the case of Xe which is the most documented, metals are synthesized above 150 GPa, i.e., at terrestrial core conditions, stoichiometric Xe-oxides between 50 and 100 GPa, i.e., in the P-T range of the Earth's lower mantle, but Xe-O high energy bonds may also form under the modest pressures of the Earth's crust (<1 GPa) in non-stoichiometric compounds. Most planetary relevant noble gas compounds found are with xenon, with only a few predicted helium compounds, the latter having no or very little charge transfer between helium and neighboring atoms.